The Organization of Islamic Cooperation : politics, problems, and potential - Kayaoglu, Turan (Abingdon, Oxon [U.K.] : Routledge, 2015)
'The Organization of Islamic Cooperation (OIC) is the world's leading international Islamic organization. Turan Kayaoglu provides the first accessible and concise introduction and overview of this important organization. This book details the OIC's struggle to address popular Muslim demands balanced against the member states' reluctance to support the OIC politically and materially. Despite this predicament, the organization has made itself increasingly relevant over the last decade through increasing its visibility as the representative body of Muslim unity and promoting its role as a reliable interlocutor on behalf of Muslims in global society. Outlining the history, workings and goals of the OIC, the book also highlights key issues that may influence the OIC's ability to realize its potential in the future.This will be of great interest to students and scholars of international relations, international organizations and islamic studies.'--
'The Organization of Islamic Cooperation (OIC) is the world's leading international Islamic organization. Turan Kayaoglu provides the first accessible and concise introduction and overview of this important organization'--
1. The origins and history of the OIC -- 2. The structure of the OIC -- 3. The OIC as a platform for intra-Muslim politics -- 4. The OIC and global issues -- 5. The OIC among global actors -- 6. The OIC and the international human rights -- 7. The OIC and the global economy -- 8. The OIC, global culture, and the dialogue of civilizations.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: Organisation of Islamic Cooperation; Islamic countries -- Politics and government